Penggunaan Verba Dalam Bahasa Jawa Di Desa Gunung Sari Kecamatan Gunung Sahilan Kabupaten Kampar - siti khusnul; Alber (Jurnal Online Baradha, 2026)
This study examines the use of Javanese verbs in everyday communication among the people of Gunung Sari Village, Gunung Sahilan District, Kampar Regency, influenced by the transmigration situation and language contact. This study aims to identify the Javanese verb forms used in everyday interactions, explain variations in their use based on speech level, and analyze social factors influencing verb choice in the community. The method used is descriptive qualitative with a sociolinguistic approach. Data were obtained from community speech, interviews, observations, and documentation of conversations in the field. The results indicate that the community still uses Javanese verbs, including the ngoko and krama forms. The ngoko form dominates daily communication, while krama is used in formal situations as a form of politeness. Furthermore, variations in speech level usage and code-mixing phenomena between Javanese and Indonesian are found in everyday interactions. Social factors such as age, social environment, social relationships, language habits, and language contact also influence verb choice. Thus, the use of Javanese verbs in Gunung Sari Village demonstrates a dynamic, adaptive, and contextual nature within a multilingual society.